An Assessment of the Effectiveness of Warfarin Therapy Monitoring Systems on Thrombophilic Patients in Zimbabwe - Maramba, Aaron; Ncube, Silenkosi; Mandisodza, Arthur; Da Silva Marques, Dayana; Matsikure, Tsehay (TH Open, 2018)
Introduction Thrombophilia describes conditions that predispose individuals to increased blood clotting and includes conditions such as deep vein thrombosis and pulmonary embolism. Thrombophilia is associated with high morbidity and mortality rates, and is commonly treated by warfarin anticoagulation. However, warfarin may cause both bleeding and clotting episodes if the therapy is not monitored and managed effectively.Objectives The main objective of this study was to assess the effectiveness of warfarin monitoring systems on thrombophilic patients at a major hospital in Zimbabwe.Material and Methods A clinical and laboratory prospective and retrospective study was performed on patients who had been on warfarin therapy for at least 1 year. Questionnaires were administered to participants on warfarin from outpatients clinics at Parirenyatwa Group of Hospitals. Their international normalized ratio (INR) results were also accessed from the laboratory information system and captured in the Epi info and Microsoft Excel for analysis.Results Fifty questionnaires were administered and 47 (94%) participants responded adequately. Twenty-nine (61.1%) participants on warfarin were females. The majority of them were elderly and in the 31 to 40 age groups. Eighteen (38.3%) participants missed their medication at some point, while 12 (25.5%) had warfarin overdose. Sixteen (34%) and 11 (23.4%) admitted to taking alcohol and smoking, respectively, while on warfarin. Thirty-five (74.5%) did not change their medication nor were advised on the right diet. Thirty-four (72.3%) had appointments set after every month. Some participants indicated that they had symptoms of both clotting and bleeding. There were statistically significant differences (p < 0.0001) between INRs for 3 monthly intervals from the initiation of warfarin therapy.Conclusion Women and the elderly formed the majority of the patients on warfarin, indicating gender and advanced age susceptibility to thrombophilia, respectively. The effectiveness of the warfarin monitoring systems appeared to be hampered by lack of a coordinated system that adequately monitors anticoagulant therapy in the country.
Keywords: anticoagulation; assessment; effectiveness; monitoring; thrombosis; warfarin